The Use of Mind Mapping Method to Develop Elementary School Students’ Writing Skills in the Cambridge Curriculum - Nyangfah Nisa Septiana; Andi Prastowo; Stevani Carolina Latuheru (Jurnal Ilmiah Sekolah Dasar, 2025)
In the current era of globalization, writing skills are very important for students. Especially in the use of the international curriculum which in its scope of subjects requires students to be able to create projects in the form of writing. Learners can be said to have writing skills when they are able to express the ideas they have in complete writing and perfect sentences. The place of this research is located in an Islamic Elementary School located. The purpose of this research is to explore or further examine the use of the mind mapping method to foster students’ writing skills. The approach used in this research is a qualitative approach with a case study method. The data collection technique was carried out through interviews through 3 participants. Data analysis in this study includes; data condensation, data presentation and conclusion. The results showed that the use of mind mapping method can foster the writing skills of elementary school students in the Cambridge curriculum. The implication of the research shows that the mind mapping method can be used as a tool to foster writing skills in the context of all subjects, to encourage learners' independence and creativity.